Management of a Subgingivally Fractured Central Incisor by Re-attachment Using a Fiber Post - Islam, Mohammad Aminul; Wakia, Tasnim; Alam, Md Shamsul; Howlader, Md Mujibur Rahman; Afroz, Shamima (Update Dental College Journal, 2014)
Reattachment of a fractured fragment to the remaining tooth is challenging but one of the best treatment protocol in regards to aesthetics, function as well as patients acceptance. This case report presents a 20 years old male with an oblique complicated crown fracture of maxillary left central incisor tooth. The procedure used to repair the fracture regarding this case included flap surgery with endodontic treatment. The root canal was filled with a root canal sealer and gutta-percha. After root canal obturation, fragments were reattached with duel cure composite resin using a glass fibre post. After 12 months evaluation, clinical and radiographic examinations showed a stable re-attachment, good aesthetics and healthy periodontium. DOI: http://dx.doi.org/10.3329/updcj.v3i1.17983 Update Dent. Coll. j: 2013; 3 (1): 37-40